Long non-coding RNA rhabdomyosarcoma 2-associated transcript contributes to neuropathic pain by recruiting HuR to stabilize DNA methyltransferase 3 alpha mRNA expression in dorsal root ganglion neuron - Guo, Xinying; Zhang, Gaolong; Cai, Weihua; Huang, Fa; Qin, Jingwen; Song, Xingrong (Frontiers in Molecular Neuroscience, 2023)
Introduction Long non-coding RNAs (lncRNAs) act as key regulators in multiple human diseases. In particular, the dysfunction of lncRNAs in dorsal root ganglion (DRG) contributes to the pathogenesis of neuropathic pain (NP). Nevertheless, the role and mechanism of most lncRNAs in NP remain unclear. Methods Two classic chronic NP models, including L4 spinal nerve ligation (SNL) model and chronic constriction injury (CCI) of the sciatic nerve, were performed. Mechanical allodynia and heat hyperalgesia were used to evaluate neuropathic pain. DRG microinjection was used to deliver agents into DRG. qRT-PCR, immunofluorescence, immunoprecipitation, western blotting, siRNA transfection, AAV transduction were performed to investigate the phenotypes and molecular basis. Results Here, we discovered that Rmst as a lncRNA was specifically expressed in Atf3+ injured DRG neurons and significantly upregulated following peripheral nerve damage. Rmst overexpression by direct DRG injection of AAV5-Rmst causes neuropathic symptoms in the absence of nerve damage. Conversely, blocking Rmst expression in injured DRGs alleviated nerve injury-induced pain hypersensitivities and downregulated Dnmt3a expression. Furthermore, we found peripheral nerve damage induced Rmst increase could interact with RNA-binding protein HuR to stabilize the Dnmt3a mRNA. Conclusion Our findings reveal a crucial role of Rmst in damaged DRG neurons under NP condition and provide a novel target for drug development against NP.